STUDENTS' CRITICAL THINKING ABILITY, CREATIVE AND LEARNING STYLE IN BAHASA INDONESIA LEARNING FOR GRADE IV SD NEGERI 112238 SEPADAN JAYA - Ariati Ariati; Isda Pramuniati; Evi Eviyanti (Jurnal Ilmiah Teunuleh, 2020)
Abstract This study aims to describe students 'critical thinking ability, students' creativity skills, and the learning style of grade 4 students at SDN 112238 Sepadan Jaya in Indonesian language lessons. This research uses qualitative descriptive method with a population of all grade 4 students at SDN 112238 Sepadan Jaya in the 2020/2021 school year of 21 students. The variables in this study were students' critical thinking ability, creativity, and learning style which included visual, auditorial and kinesthetic. Data collection techniques using questionnaires and analysis techniques used are descriptive statistics. The results showed that the average grade 4 at SDN 112238 Sepadan Jaya in the 2020/2021 school year in Bahasa Indonesia has the majority ability in the highly critical thinking category, at around 47.6%. Ability majority in the creative category, in percentage about 66.67%. The majority of learning styles are Kinesthetic, students have a tendency to one of the visual, auditory or kinesthetic learning styles, with the average student having a tendency on visual learning style 33.33%, auditory learning style 14.28%, and kinesthetic learning style 52.38%.